2018
DOI: 10.1101/385468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circuit Degeneracy Facilitates Robustness and Flexibility of Navigation Behavior in C.elegans

Abstract: 20Animal behaviors are robust and flexible. To elucidate how these two conflicting 21 features of behavior are encoded in the nervous system, we analyzed the neural circuits 22 generating a C. elegans thermotaxis behavior, in which animals migrate toward the past 23 cultivation temperature (T c ). We identified multiple circuits that are highly overlapping 24 but individually regulate distinct behavioral components to achieve thermotaxis. When 25 the regulation of a behavioral component is disrupted foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 83 publications
(131 reference statements)
0
11
0
Order By: Relevance
“…To address how the alteration in the modes of the AFD-AIY communication contributes to the regulation of TTX behavior, we undertook multiworm tracking analysis (42). We classified the animal behavior into several behavioral components discernable during C. elegans locomotion, such as forward locomotion, omega turn, shallow turn, reversal, and reversal turn (43)(44)(45)(46)(47). Previous studies showed that the wild-type animals modulate the run durations such that the duration of run toward the cultivation temperature would be lengthened (20, 48-50).…”
Section: Alteration Of the Afd-aiy Synaptic Transmission Requires Commentioning
confidence: 99%
See 1 more Smart Citation
“…To address how the alteration in the modes of the AFD-AIY communication contributes to the regulation of TTX behavior, we undertook multiworm tracking analysis (42). We classified the animal behavior into several behavioral components discernable during C. elegans locomotion, such as forward locomotion, omega turn, shallow turn, reversal, and reversal turn (43)(44)(45)(46)(47). Previous studies showed that the wild-type animals modulate the run durations such that the duration of run toward the cultivation temperature would be lengthened (20, 48-50).…”
Section: Alteration Of the Afd-aiy Synaptic Transmission Requires Commentioning
confidence: 99%
“…S8A, and see also ref. 43). In addition, consistent with the previous reports of regulation of run duration during TTX (20, 48-50), we observed that the wild-type animals exhibited a significant bias in the frequency of reversal turn.…”
Section: Alteration Of the Afd-aiy Synaptic Transmission Requires Commentioning
confidence: 99%
“…6), we found that the curve, change in the moving direction during forward locomotion, was one such component (Fig. 6a): the wild-type animals behaving below the cultivation temperature showed curving bias toward warmer temperature when migrating up the thermal gradient, while they curve toward colder temperature above the cultivation temperature 36 (Fig. 6a), suggesting that this regulation of the curve would drive the animals toward the cultivation temperature.…”
Section: Resultsmentioning
confidence: 93%
“…To address how the alteration in the modes of the AFD-AIY communication contributes to the regulation of thermotaxis behavior, we undertook multi-worm tracking analysis 35 . We classified the animal behavior into several behavioral components discernable during C. elegans locomotion, such as forward locomotion, turns and reversals 36 . We sought the behavioral components that were oppositely biased below or above the cultivation temperature in the wild-type animals, and were oppositely affected by the cryophilic ( kin-4 and dgk-1 ) or thermophilic ( mec-2 ) mutations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation